PEMANFAATAN LIMBAH KULIT PISANG MENJADI PAKAN IKAN HERBAL DENGAN TEKNOLOGI MURTASENG MELALUI PEMBERDAYAAN KELOMPOK BUDIDAYA PERIKANAN FAJAR MINA SEJAHTERA, LAMPUNG TIMUR - Qulubi, M. Hadziq; Mandala, Wintari; Utami, Endang Sri (Universitas Mataram, 2024)
Pokdakan Fajar Mina Sejahtera is a freshwater fish farming group in Taman Fajar Village, East Lampung Regency with tilapia and carp as the main commodities. The higher price of feed followed by the COVID-19 pandemic has caused the cessation of fish farming activities. Through Pengabbdian kepada Masyarakat (PkM) or local community service activities, mentoring are carried out for Pokdakan to provide awareness of the importance of the sustainability of fish farming activities with the potential for abundant natural resources. This activity aims to revive fish farming activities with assistance in making feed independently and at low production costs. Feed producing is carried out by utilizing banana peel waste in local area using the Murtaseng method. The assistance of the program is carried out through three stages, namely preparation, implementation, and evaluation. The success of Pokdakan empowerment activities in herbal feed production reached 80%. The widespread information about this success has attracted local community in the production of herbal feed. This made the PkM implementation team create a follow-up concept to assist again for increasing the capacity of Pokdakan. This further assistance is more focused on business management. The Pokdakan Empowerment activity has resulted in the independence of the fish farming production process comprehensively. The sustainability of fish farming activities by Pokdakan of Fajar Mina Sejahtera is expected to trigger the creation of an independent community both economically, socially and food security.